Potential blood-based biomarkers for cognitive frailty: a narrative review / Wan Suraya Wan Nazahar ... [et al.] - Wan Nazahar, Wan Suraya; Siong, Meng Lim; Abdul Majeed, Abu Bakar; Ramasamy, Kalavathy (Faculty of Pharmacy, 2023)
Cognitive frailty (CF), which refers to the coexistence of physical frailty and cognitive impairment, is predicted to rise as the global aged population continues to grow. As such, reliable biomarkers are needed to facilitate diagnosis. It is hypothesised that blood-based biomarkers, which are non-invasive, simple and inexpensive, may be useful for diagnosis of CF. The current narrative review was undertaken to perform a literature search of journals on blood-based biomarkers for CF published between 2016-2021 and to critically review the relevant journals. The literature search for published journals was performed using ScienceDirect and PubMed, and was facilitated by a combination of keywords which included blood biomarkers and CF. Further to the processes of screening and checking of published literature for eligibility based on inclusion and exclusion criteria, 19 articles were shortlisted and critically reviewed. Basically, tryptophan, C-reactive protein (CRP), total cholesterol and vitamin D were found to be the major blood-based biomarkers for CF as they were all reported by at least 2 studies. On average, tryptophan levels in CF group were 1.4 times lower than control. The majority of the blood-based biomarkers of CF were involved in amino acid (AA) metabolism and inflammatory response pathways. In general, blood-based biomarkers (i.e., tryptophan, CRP, total cholesterol and vitamin D) may be useful for diagnosis of CF but require further studies.